Herbicide-resistant forms of Arabidopsis thaliana acetohydroxyacid synthase: characterization of the catalytic properties and sensitivity to inhibitors of four defined mutants. - Chang, A K (1998)
Acetohydroxyacid synthase (AHAS) catalyses the first step in the synthesis of the branched-chain amino acids and is the target of several classes of herbicides. Four mutants (A122V, W574S, W574L and S653N) of the AHAS gene from Arabidopsis thaliana were constructed, expressed in Escherichia coli, and the enzymes were purified. Each mutant form and wild-type was characterized with respect to its catalytic properties and sensitivity to nine herbicides. Each enzyme had a pH optimum near 7.5. The specific activity varied from 13% (A122V) to 131% (W574L) of the wild-type and the Km for pyruvate of the mutants was similar to the wild-type, except for W574L where it was five-fold higher. The activation by cofactors (FAD, Mg2+ and thiamine diphosphate) was examined. A122V showed reduced affinity for all three cofactors, whereas S653N bound FAD more strongly than wild-type AHAS. Six sulphonylurea herbicides inhibited A122V to a similar degree as the wild-type but S653N showed a somewhat greater reduction in sensitivity to these compounds. In contrast, the W574 mutants were insensitive to these sulphonylureas, with increases in the Kiapp (apparent inhibition constant) of several hundred fold. All four mutants were resistant to three imidazolinone herbicides with decreases in sensitivity ranging from 100-fold to more than 1000-fold.